Physicochemical properties of vegetable leather made from broccoli stems (Brassica oleracea var. italica) with the addition of pectin - Safinta Nurindra Rahmadhia; Ummu Nur Saadah; Ali Jebreen (AGROINTEK, 2025)
Vegetable leather is a product that comes from dried vegetable puree in the form of flexible sheets. It has a chewy texture that can be consumed as a snack. Broccoli stems are vegetables that are rarely used to their full potential. The problem that often arises with vegetable leather is its poor elasticity. This research aims to determine the physicochemical properties of the broccoli stem vegetable leather. The production of vegetable leather was done by mixing broccoli stems and pectin in various concentrations (F1 (99.5% and 0.5%), F2 (99% and 1%), F3 (98.5% and 1.5%), F4 (98% and 2%).Furthermore, the mixture was dried to form a thin sheet. Then, broccoli stems and vegetable leather were analyzed for their physical and chemical properties such as texture, water content, ash content, reducing sugar, vitamin C, and crude fiber. The results showed that the addition of pectin had a significant effect on the physical properties of the texture, namely hardness 599.62N to 752.82N, gumminess 560.84N to 751.01N, chewiness 511.34N to 685.49N and do not show a significant effect for cohesiveness 0.9074 to 0.9750. Chemical properties have a significant effect on water content values 11.92% to 13.16%, reducing sugar 8.52% to 9.90%, vitamin C 40.15mg/100g to 44.58mg/100g, crude fiber 9.48% to 11.61%, and ash content 2.14% to 2.25%. The incorporation of broccoli stem with additional pectin to produce vegetable leather constitutes a food rich in fiber and vitamins. By-products of broccoli can be turned into nutritionally beneficial foods.